A Study on determinants of Customer Satisfaction Towards Broadband Services in Songkhla Province - Laeheem, Miss Fateemoh (2012)
The researcher studies the determinants or the key factors that can affect the level of customer satisfaction of the Broadband Services in Songkhla Province in Thailand. It is crucial that Internet is a part of life for the business people in today. It can be mentioned that factors influencing between internet service of all Broadband Services providers in Songkhla Province in Thailand, quality, speed of internet and price are influential for the decision making process of the customers to select the Broadband Services providers in Songkhla Province in Thailand. The questionnaires for the quantitative research conduct were developed from many previous researches. The data was collected from 100 randomly respondents which focused business group. In addition to this, the Pearson’s Correlation Coefficient Analysis, Chi-square (2) and ANOVA (F-Test) were used to test the hypotheses of this study. In further, the results of this study show that the price and quality of Broadband Services providers are significant relevant to the customers’ satisfaction in the part of finding and analysis accordingly. Whereas, the stability, education, and monthly income have no relevant to the customers’ satisfaction in Songkhla Province in Thailand.